2001
DOI: 10.1007/pl00000235
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanisms involved in the inflammatory response induced by des-Arg9-bradykinin in the rat pleural cavity

Abstract: These findings suggest that inflammatory responses caused by the B1 agonist des-Arg9-BK in the rat pleural cavity are mediated by a receptor-independent mechanism, being largely dependent on the activation of resident mast cells and release of histamine and/or serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Blocking of both receptors also displayed cell adhesion molecule expression modulation, which supports the existence of alternative pathways for the regulation of endothelium-leukocyte adhesion interaction (47)(48)(49). Such regulation seems to be dependent on cytokines, LPS, or other mediators of inflammation independent of bradykinin B1 and B2 receptor pathways (49). Although angiogenesis is an important process in the development and perpetuation of rheumatoid arthritis, there was no difference among the disease-untreated and treated groups.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Blocking of both receptors also displayed cell adhesion molecule expression modulation, which supports the existence of alternative pathways for the regulation of endothelium-leukocyte adhesion interaction (47)(48)(49). Such regulation seems to be dependent on cytokines, LPS, or other mediators of inflammation independent of bradykinin B1 and B2 receptor pathways (49). Although angiogenesis is an important process in the development and perpetuation of rheumatoid arthritis, there was no difference among the disease-untreated and treated groups.…”
Section: Discussionmentioning
confidence: 65%
“…This hypothesis could be tested by use of a B1 receptor agonist; however, the response may be limited by the development of tachyphylaxis (45,46). Blocking of both receptors also displayed cell adhesion molecule expression modulation, which supports the existence of alternative pathways for the regulation of endothelium-leukocyte adhesion interaction (47)(48)(49). Such regulation seems to be dependent on cytokines, LPS, or other mediators of inflammation independent of bradykinin B1 and B2 receptor pathways (49).…”
Section: Discussionmentioning
confidence: 96%
“…The use of ACEi has been associated with the occurrence of side effects such as AE [11,12]. Accumulation of kinins namely bradykinin (BK) or its metabolites has been suggested to be involved in these effects [12][13][14]. The knowledge of the in vivo profile of two dual ACE/NEP inhibitors, which are currently undergoing clinical trials in terms of kinins (bradykinin, BK1-8 and other metabolites) accumulation, should be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, their use in the clinic is limited because they have been associated with the occurrence of side effects such as AE [11,12]. The mechanism of AE remains unresolved, however, several studies performed in rats or in humans suggested that accumulation of BK and that of its metabolite BK1-8 in plasma may participate in the occurrence of AE [12][13][14]. Because it is important to have active but also safe compounds, a new class of cardiovascular drugs that simultaneously inhibit both ACE and NEP has been developed (for a review see ref [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a number of authors show that when intrapleural injection of des-Arg9-BK occurs with a temporary dependence of migration of the inflammatory cell, characterized mainly by the use of mononuclear cells and neutrophil cells [5].…”
Section: амурский медицинский журнал №3 (19) 2017mentioning
confidence: 99%